Research Progress of Preparing Titanium Alloy By Molten Salt Method - Miao, Yuhang; Cai, Yanqing; Ren, Mengya; Hu, Jinming (International Journal of Natural Resources and Environmental Studies, 2024)
Titanium alloy has excellent characteristics that cannot be compared with other metals such as light specific gravity, high specific strength, wide applicable temperature range, corrosion resistance, and hydrogen storage. The traditional titanium alloy smelting process is mainly based on titanium sponge as raw material, which has a long process, high energy consumption, heavy pollution, and other problems, which seriously restricts the sustainable development of titanium alloy in the world. The common methods of preparing titanium alloy are alloy melting, metal thermal reduction, powder metallurgy, and the gradually emerging molten salt electrolysis. Among them, molten salt electrolysis is recognized as the most promising method to replace the traditional titanium alloy production process, and certain achievements have been made in recent years in terms of both process and basic theory research. In this paper, the common processes of titanium alloy preparation by molten salt electrolysis at home and abroad, such as molten salt electrolytic co-deposition method, cathodic alloying method and liquid cathode method, new FFC method, and its derived SOM method, etc., will be summarized systematically, and the future research will be put forward.